2017
DOI: 10.1097/ccm.0000000000002335
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-Specific Enolase Predicts Poor Outcome After Cardiac Arrest and Targeted Temperature Management: A Multicenter Study on 1,053 Patients

Abstract: High neuron-specific enolase serum concentrations reliably predicted poor outcome at ICU discharge. Prediction accuracy differed and was better for out-of-hospital cardiac arrest than for in-hospital cardiac arrest patients. Our "in-the-field" data indicate 90 μg/L as a threshold associated with almost no false positives at acceptable sensitivity. Confounders of neuron-specific enolase elevation should be actively considered: neuron-specific enolase-producing tumors, acute brain diseases, and hemolysis. We str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
65
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 27 publications
11
65
0
2
Order By: Relevance
“…Besides, S-100B, an acidic protein with a calcium binding motif produced by astroglial cells in the brain, is a predictive marker for outcome of patients after cardiac arrest [8]. Neuron specific enolase (NSE), another a neural protein primarily produced by neurons and is leaked into the extracellular space after severe injury, is also a useful predictor of outcome in PCAS patients [9]. Lipocalin, might predict the neurological outcomes of PCAS patients, and its predictive value was equivalent to that of NSE [10].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, S-100B, an acidic protein with a calcium binding motif produced by astroglial cells in the brain, is a predictive marker for outcome of patients after cardiac arrest [8]. Neuron specific enolase (NSE), another a neural protein primarily produced by neurons and is leaked into the extracellular space after severe injury, is also a useful predictor of outcome in PCAS patients [9]. Lipocalin, might predict the neurological outcomes of PCAS patients, and its predictive value was equivalent to that of NSE [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of HIE, since CSF‐NSE was increased when neurons turned degenerative and necrotic, and the serum NSE (s‐NSE) level was elevated due to BBB disruption, both s‐NSE and CSF‐NSE could be deemed as the biomarkers for indicating the severity and prognosis of neuron damages (Noaman et al., ; Varsami et al., ). For instance, when the cut‐off value of NSE was set as ≥45.4 μg/L, the sensitivity and specificity of s‐NSE for diagnosing medium and severe HIE were, respectively, 79% and 70% (Streitberger et al., ). However, applying NSE for diagnosing HIE was still unsatisfactory, for that the increased NSE could also be found within other disorders, including neonatal hyperbilirubinemia, infectious brain injury, and brain injury caused by congenital metabolic diseases (Gazzolo et al., ; Yao, Zhang, Ai, Liu, & Huang, ).…”
Section: Discussionmentioning
confidence: 99%
“…10 A similar European study prospectively analysed NSE serum concentrations in >1000 patients who were cooled to 33 C after cardiac arrest. 11 They found that high concentrations reliably predicted poor outcome at critical care discharge. 11 While biomarker use is uncommon in current UK practice, interpretation should be in combination with other forms of testing.…”
Section: Biomarkersmentioning
confidence: 99%
“…11 They found that high concentrations reliably predicted poor outcome at critical care discharge. 11 While biomarker use is uncommon in current UK practice, interpretation should be in combination with other forms of testing.…”
Section: Biomarkersmentioning
confidence: 99%